2022
DOI: 10.1155/2022/8509626
|View full text |Cite|
|
Sign up to set email alerts
|

mRNA-Modified FUS/NRF2 Signalling Inhibits Ferroptosis and Promotes Prostate Cancer Growth

Abstract: Objective. Regarding the imperfect mechanism of occurrence and development of prostate adenocarcinoma (PRAD), this study investigated mRNA-modified FUS/NRF2 signalling to inhibit ferroptosis and promote prostate adenocarcinoma growth. Methods. Bioinformatics analysis was used to obtain the expression of FUS and its mRNA modification in PRAD. The expression of FUS in prostate cells (CRPC) and the level of m6A methylation modification, ferroptosis (P53 and GPX4), apoptosis (Caspase3), ferroptosis (P53 and GPX4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A previous study revealed that, as a famous RNA‐binding protein, FUS was able to bind to and stabilize the NRF2 mRNA. 16 Here, we verify the regulation of FUS protein on NRF2 expression in SW1990 cells. Our RNA‐IP results showed that FUS protein is directly bound to NRF2 mRNA (Figure 9A ).…”
Section: Resultsmentioning
confidence: 74%
“…A previous study revealed that, as a famous RNA‐binding protein, FUS was able to bind to and stabilize the NRF2 mRNA. 16 Here, we verify the regulation of FUS protein on NRF2 expression in SW1990 cells. Our RNA‐IP results showed that FUS protein is directly bound to NRF2 mRNA (Figure 9A ).…”
Section: Resultsmentioning
confidence: 74%
“…Nrf2 is also involved in activating different target genes of iron/GSH metabolism to prevent lipid peroxidation and ferroptosis ( Wang et al, 2016 ). Targeting Nrf2 or inhibiting cysteine/GSH metabolism causes uncontrolled oxidative stress and siderotoxicity, thereby arresting tumor growth and triggering iron-dependent cell death ( Wang et al, 2022 ).…”
Section: Ferroptosis In Cancersmentioning
confidence: 99%
“…The overexpression of HECT and Copper Zinc Superoxide Dismutase Domain containing protein 1 (HACE1) in glioma tissues competes with Keap1 to prevent Nrf2 from being degraded via ubiquitination at the post-translational modification level and promotes the upregulation of Nrf2 transcriptional expression via the internal ribosome entry site (IRES) through La/SSB [ 76 ]. Targeting Nrf2 can induce ferroptosis in PCa cells [ 77 ], providing novel insight into the radiotherapy resistance of PCa. Therefore, Nrf2 is a critical target for improving treatment resistance in PCa [ 78 , 79 ].…”
Section: Disruption Of Cellular Redox Homeostasismentioning
confidence: 99%